SEDIMENT BIOTURBATION POTENTIAL of UCA RAPAX and UCA URUGUAYENSIS AS A RESULT of THEIR FEEDING ACTIVITY - Sayao-Aguiar, Bruno [UNESP]; Amaro Pinheiro, Marcelo Antonio [UNESP]; Colpo, Karine Develati [UNESP] (Crustacean Soc, 2012)
Bioturbation of mangrove sediments by Uca uruguayensis (Nobili, 1901) and U. rapax (Smith, 1870) was compared based on the grain-size composition and organic content in surface sediment around the burrow and feeding pellets in two mangrove zones of the Sao Vicente Estuary, state of São Paulo, Brazil. For each species, 25 burrows with active crabs were selected. All pellets within a 15-cm radius of each burrow were carefully collected; samples of substrate were taken; and the crab occupant was excavated, sexed, and measured for carapace width (CW). The number of spoon-tipped setae on the second maxilliped of each species was estimated; U. uruguayensis showed more of these setae than U. rapax. For both species, the sediment post-processed by feeding activity (feeding pellets) showed a similar increase of coarser fractions and a smaller organic content. However. U. uruguayensis was more efficient in removing organic matter (88.1%) from the sediment than U. rapax (37.5%). These results suggest that different numbers of spoon-tipped setae on the second maxillipeds of the fiddler crabs do not affect the potential for grain-size selection, but result in differing abilities to remove organic matter from the sediment.
Keywords: feeding pellets; mangrove; sediment particle size; spoon-tipped setae; Uca